Phytosociological study of seed plants in Isla balabag, Taklong Island National Marine Reserve, Nueva Valencia, Guimaras, Philippines. - Zabala, Zsareena Bianca R.
Islands with area less than 1000 km2 are already considered as small islands. These islands, due to its size and isolation, are pron to climate change, sea-level rise, habitat loss and biological invasion. The Philippine archipelago is composed of 7,641 islands. Owing to its varied topography, the country is rich in biodiversity and forest types. However, flora of small islands has not been extensively studied despite the threats to them. There is little information available on their diversity and community structure. Thus, this study was initiated in an attempt to provide new data, at least for this part of the country. The floristic diversity and community structure of Isla Balabag as part of Taklong Island National Marine Reserve was described by laying out six random plots (10x10m). Physico-chemical parameters such as temperature, relative humidity, soil temperature, elevation, and size of the island were determined. Plant description, herbarium and identification were done. There were 44 species distributed among 25 families on the island. The three plant forms found here were trees, shrubs and vines. Out of 44 species, 37 were identified and 7 could not be placed in any taxon due to absence of key plant characters such as flowers and fruits. Fabaceae has the highest species composition. There are two types of vegetation in the island: mangrove and beach formation. Beach formation is divided into three: pes-caprae formation, mixed shrub-tree zone and mixed forest. The total SBA of Isla Balabag is 24.50 m2 ha-1. Therminalia foeditissima is the most dominant species because it has the largest stand basal area. Streblus asper is the most important species because of its high frequency and density. The height of the species ranges from 2.8 to 8.9 meters. The species diversity of the island is 0.40 which was obtained using Shannonn-Weiner diversity index. Isla Balabag has a small size and evaluation which is the reason why it has a low diversity. The species evenness (0.28) is also low which indicates that dominating species were present.